2021
DOI: 10.1007/s42995-021-00100-3
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic insights into the effects of submerged plants on functional potential of microbial communities in wetland sediments

Abstract: Submerged plants in wetlands play important roles as ecosystem engineers to improve self-purification and promote elemental cycling. However, their effects on the functional capacity of microbial communities in wetland sediments remain poorly understood. Here, we provide detailed metagenomic insights into the biogeochemical potential of microbial communities in wetland sediments with and without submerged plants (i.e., Vallisneria natans). A large number of functional genes involved in carbon (C), nitrogen (N)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…The zOTUs of gut microbiota and networked communities (assemblages of microbial taxa detected in the networks), as well as parameters calculated accordingly involved one individuals or all of the following statistical analyses: (i) alpha-diversity comparisons were conducted to reveal dynamics of gut microbiota throughout zebrafish development as visualized by sampling points and developmental stages; (ii) significance tests were performed through an ANOVA with least-significant-difference (LSD) to examine whether differences among comparisons were significant or not; (iii) correlation analysis was performed to ascertain whether the characteristics interested were significantly correlated or not ( 61 ); (iv) nonparametric dissimilarity tests including multiple-response permutation procedure (MRPP) and permutational multivariate analysis of variance (PERMANOVA) tests were performed to compare community dissimilarities based on Bray-Curtis and Jaccard distances, respectively ( 62 ); (v) ternary plots, Venn plots, and DCA were used to compare the networked communities among stages as with our previous study ( 63 ). All the statistical analyses were performed based on the R software (R Foundation for Statistical Computing, Vienna, Austria) if not specified otherwise.…”
Section: Methodsmentioning
confidence: 99%
“…The zOTUs of gut microbiota and networked communities (assemblages of microbial taxa detected in the networks), as well as parameters calculated accordingly involved one individuals or all of the following statistical analyses: (i) alpha-diversity comparisons were conducted to reveal dynamics of gut microbiota throughout zebrafish development as visualized by sampling points and developmental stages; (ii) significance tests were performed through an ANOVA with least-significant-difference (LSD) to examine whether differences among comparisons were significant or not; (iii) correlation analysis was performed to ascertain whether the characteristics interested were significantly correlated or not ( 61 ); (iv) nonparametric dissimilarity tests including multiple-response permutation procedure (MRPP) and permutational multivariate analysis of variance (PERMANOVA) tests were performed to compare community dissimilarities based on Bray-Curtis and Jaccard distances, respectively ( 62 ); (v) ternary plots, Venn plots, and DCA were used to compare the networked communities among stages as with our previous study ( 63 ). All the statistical analyses were performed based on the R software (R Foundation for Statistical Computing, Vienna, Austria) if not specified otherwise.…”
Section: Methodsmentioning
confidence: 99%
“…However, we know that the identification of keystone groups by such methods is not adequate, and more methods and experimental designs are needed to demonstrate the role of these keystone taxa in the ecological network. 50 , 51 …”
Section: Discussionmentioning
confidence: 99%
“…The bacterial cell wall traits (e.g., flagella and cell wall components), bacterial secretion, and oxidative stress response determine the success of protist predation on bacteria . For instance, bacterial flagella provide high motility and thereby probably bacterial retraction upon contact with protists to prevent capture. , In addition, bacterial secondary metabolites or toxic products (Shiga toxin, lytic enzymes, and the volatile compound hydrogen cyanide) provide efficient protection against predators. , The reactive oxygen species (ROS) produced by bacteria is an important indicator of the degree of biological or abiotic stresses on bacteria . Previous studies also indicated that biotic stress might affect the synthesis of bacterial redox-active compounds (e.g., c -type cytochrome, quinone, and flavins), which can directly provide electrons for the reduction of [Fe­(III), Cr­(VI) and U­(VI)] .…”
Section: Introductionmentioning
confidence: 99%